Visual Exploration Strategies and the Development of Infants’ Facial Emotion Discrimination - Amso, Dima; Fitzgerald, Megan; Davidow, Juliet; Gilhooly, Tara; Tottenham, Nim (Frontiers in Psychology, 2010)
We examined the role of visual exploration strategies in infants’ discrimination between facial emotion expressions. Twenty-eight 6-11-month-olds were habituated to alternating models posing the same expression (happy N =14 /fearful N = 14) as eye gaze data were collected with a corneal reflection eye tracker. Gaze behavior analyses indicated that duration of gaze to the eyes and mouth was similar, consistent with what would be expected based on area subtended by those regions, and negatively correlated. This pattern did not differ as a function of age, sex, or habituation condition. There were no posthabituation performance differences as a function of age group (6-8 month- versus 9-11 month-olds). Only infants habituated to happy faces showed longer looking at the novel emotion (fear) when the model was held constant from habituation to test. We found no reliable correlation between this performance and proportion of gaze directed at any one facial region. Consistent with previous work, the group habituated to fear faces showed no reliable posthabituation novelty preference. Individual differences in gaze behavior shed light on this finding. Greater proportion of gaze directed at the eyes correlated positively with preference for the novel emotion (happy). These data suggest that, as in other object classes, visual exploration strategies are an important agent of change in infants’ capacity to learn about emotion expressions. (218 words)